Pertumbuhan Brassica chinensis L. pada Pot Batang Pisang dengan Pemupukan NPK dan Guano - Listiatie Budi Utami; Mila N Saragih (Universitas Sebelas Maret, 2023)
Brassica chinensis L is a vegetable plant that grows well in moist media. This media needs to be supported by place that can maintain humidity. One alternative is a pot made from banana stem waste. Brassica or caisim grown in banana stem pots requires adequate nutrition. The aim of this research was to determine the growth response of caisim and determine the best dose of inorganic NPK fertilizer and organic Guano fertilizer for the growth of caisim in potted banana stems. This research used RAKL consisting of 2 treatments of NPK and Guano fertilizer types with different dosage levels carried out in a total of 3 repetitions. Caisim plants are planted on banana stem planting media and consist of K as a control without fertilizer, NPK fertilizer (N1: 6.25 grams/pot; N2: 12.5 grams/pot; N3 25.0 grams/pot) and fertilizer. Guano (G1 6.25 grams/pot; G2 12.5 grams/pot; G2: 25.0 grams/pot). The response of caisim mustard plants to different doses of NPK fertilizer and Guano fertilizer was shown in the vegetative growth phase which included plant height, number of leaves, leaf area, fresh weight and dry weight. The research results showed that Caisim using banana stem pots showed varying growth at various doses of both organic Guano and inorganic NPK fertilizers. The conclusion of this study is that caisim growth respond spositively to the administration of various doses of Guano fertilizer and NPK. Caism growth on Guano fertilizer 25.0 g showed the best results among all the doses of fertilizer given.